Business Feasibility Study Training for PKK Seruni RT.017, Mangun Jaya Village, Tambun District, Bekasi, West Java - Sumiyarti, Sumiyarti; Nurhayati, Nurhayati; Maria Winata (International Journal of Community Service Implementation, 2024)
The PKK RT 017 group is pioneering productive activities in the form of a joint business of making mini pastel cookies and onde ketawa. The production is branded “Seruni17” in accordance with the name of the PKK dasawisma. The problem faced by this business group is that the quality of production is not good and there is no business feasibility analysis underlying the running of the business. Therefore, the purpose of this PkM activity is to assist partners in improving product quality and making business feasibility calculations. To achieve these objectives, the implementation team conducted training in the form of cooking classes and training on assessing business feasibility using the Benefit Cost Ratio (B/C ratio) formula. Training activities were carried out using lecture, question and answer and practice methods. In general, the PkM activities carried out have given positive and significant results to the PkM activities. The results achieved by the participants can be seen from the better quality of the products, and the feasibility of the business being run. Based on the B/C Ratio method, the results show that the business is economically feasible.